: (Case Study on Financial Companies Listed on the Indonesia Stock Exchange 2019 – 2022) - Indana Zahrotul Aini; Abi Suryono; Kusumaningdiah Retno Setiorini; Citra Amelia Putri; Nila Hidayah (STIE PGRI Dewantara Jombang, 2024)
This study examines the effectiveness of mandatory auditor switching regulations related to the failure of audits of companies' financial statements on the Indonesia Stock Exchange (IDX), including those conducted by affiliates of the Big Four Public Accounting Firm (PAF). This study analyzes the effect of mandatory auditor switching on departing partners, replacement partners, and PAF reputation on audit quality, with control variables such as company size, financial leverage, profitability, and company losses. Using data from financial sector companies on the IDX for the period 2019–2022, this study applies purposive sampling and obtains 132 samples. Logistic regression analysis was performed using SPSS version 25. The results show that, simultaneously, the three main variables affect audit quality. However, partially, mandatory auditor switching on departing and replacement partners does not have a significant effect, while PAF's reputation has a positive impact on audit quality.